(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduced the topological dual B-homomorphism in a topological dual B-algebras and its example. Moreover, this paper also presented a Python program to check the homomorphism condition of the topological dual B-homomoprphism. Furthermore, the topology for the quotient dual B-algebra was presented using the natural dual B-homomorphism. This quotient dual B-topological space was proven to be a topological dual B-algebra. Consequently, properties of a topological homomorphism were determined. The topological dual B-isomorphisms among topological dual B-algebras was also introduced and some results were obtained.